Relationship Of Inflammatory Biomarkers and Glycemic Control In Pre And Postmenopausal Women With Type 2 Diabetes Mellitus - Ayub, Saddaf; Zainub, Abeerah; Khan, Wajahat Ullah; Jahan, Saira; Ghulam, Bushra; Rehman, Bushra (Journal of Rawalpindi Medical College, 2024)
Objective: To determine whether postmenopausal status is associated with elevated plasma inflammatory markers ferritin, neutrophil to lymphocyte ratio NLR, platelet to lymphocyte ratio PLR) compared to premenopausal status in women with type 2 diabetes mellitus and to establish a correlation between inflammatory markers and glycemic status in pre-and post-menopausal diabetic women. Methods: A total of 80 participants aged 25-75 were recruited, from January 2024 to April 2024 and were divided into pre- and postmenopausal groups (Group I and II respectively) based on history using convenient sampling. Clinical assessments included general physical exams and BMI calculations. The biochemical analysis involved measuring Glycosylated haemoglobin (HbA1c), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and ferritin levels. The study examined the inflammatory profiles linked to menopausal status in diabetic patients. Results: HBA1c levels were significantly higher (P < 0.05)in Group I than in Group 2 (median 9.35 [interquartile range: 8.0 – 10.4] versus 7.10 [interquartile range: 6.42 – 8.37] Also serum ferritin levels in Group I were significantly higher (P < 0.05) as compared to Group II (median 173 [interquartile range: 100-190] versus 35.14 [interquartile range: 8.12 – 52.75]. PLR showed significant differences (P < 0.05) between the two groups, the ratio being higher in Group II as compared to Group I (median 108 [interquartile range: 85.38-132.77] versus 74.10 [interquartile range: 69.88-85.12]There was significant negative association between HbA1C and ferritin in both premenopausal and postmenopausal diabetic patients. However, there is no significant correlation between HbA1C and NLR or PLR in either group. Conclusion: The interaction between menopause and T2DM affected the platelet-to-lymphocyte ratio but not the neutrophil-to-lymphocyte ratio. Also, ferritin levels are decreased in postmenopausal diabetic women. Further, glycemic status is not the only risk factor for predicting inflammation in diabetics, other risk factors have to be catered to evaluate the inflammation status of diabetic pre and postmenopausal females. Keywords: Inflammation, neutrophil to lymphocyte ratio, Platelet to lymphocyte ratio, Ferritin, HbA1c, premenopausal women, postmenopausal women, Diabetes Mellitus.